Hearing preservation after radiotherapy for vestibular schwannomas is comparable to hearing deterioration in healthy adults and is accompanied by local tumor control and a highly preserved quality of life (QOL) as patients' self-reported outcome - Combs, Stephanie E.; Welzel, Thomas; Kessel, Kerstin; Habermehl, Daniel; Rieken, Stefan; Schramm, Oliver; Debus, Juergen (Radiotherapy and Oncology, 2013)
Purpose: To evaluate long-term results and patients' self-reported outcome of high-precision photon radiotherapy for the treatment of patients with vestibular schwannoma (VS). Methods and materials: We treated 246 patients with 248 VS with fractionated stereotactic radiotherapy (FSRT) or stereotactic radiosurgery (SRS). For FSRT, a median total dose of 57.6 Gy was prescribed in median single doses of 1.8 Gy, for SRS, a median dose of 13 Gy/80% isodose was applied. Of all patients, 51 patients died during follow-up. To evaluate long-term toxicity and QOL, we sent out a questionnaire to all living patients; of these, 81 patients (42%) sent back the questionnaire. Results: Median local control was 84 months, actuarial local control rates for both groups (SRS and FSRT) were 98% after 2, 95% after 5, and 93% after 10 years; there was no statistical difference between FSRT and SRS. Hearing deterioration was significantly higher in the SRS group than the FSRT group. However, when comparing FSRT to SRS with doses ≤ 13 Gy, hearing preservation is comparable. In patients with useful hearing, hearing preservation was 89.7% at 1 year, 84.7% at 3 years, 76.5% at 5 years, and 68.6% at 10 years. After 10 years of follow-up, hearing deterioration can be observed in both subgroups. In the FSRT group, facial nerve toxicity rate was 1.6%. Trigeminal nerve toxicity was observed in 2.1% after FSRT. Overall QOL was unchanged in 47% of the patients after RT, and 31% reported an improvement in QOL during follow-up. Conclusion: Patients' self-reported outcome confirms good results with respect to tumor control and QOL after FSRT or SRS in patients with VS. SRS can be associated with higher side effect following a dose-dependency. In long-term follow-up, hearing deterioration is most likely attributed to normal aging, but not treatment-related. © 2012 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Acoustic neuroma; Hearing preservation; Local control; Radiation; Radiosurgery